Perancangan Sistem Informasi Analisa Website Penjualan Mobil menggunakan Metode Webqual 4.0 - Fransisca Angellina Wijaya; Popon Handayani (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2023)
The existence of the internet is no longer foreign to almost all circles of society. Internet has become one of the important needs in everyday lives, especially in information exchange. Utilization of the internet can’t be separated from the existence of website, a place where the information needed by the user is located. To attract the attention of visitors, a website should have an attractive, communicative, and user-friendly appearance. This research was conducted at PT. Sejahtera Buana Trada – Suzuki Pantai Indah Kapuk (PIK), where the sample used in this study are consumer PT.SBT – PIK totaling 100 people. To determine the sample, Webqual 4.0 method is used in which data is collected through interview and questionnaires. The data analysis technique used validity test and reliability test, then to calculate the data results used quantitative descriptive analysis methods. From the test results based on the usability aspect, the percentage is 96,25%, the Information Quality aspect is 96,77%, the Service Interaction Quality aspect is 85,75%, and Overall Impression is 87,40%. Results The average of the four aspects obtained a percentage of 91,54%. So it can be concluded that the highest aspect is Information Quality, while the lowest aspect is Service Interaction Quality.